2019
DOI: 10.1021/acs.jpcb.9b08557
|View full text |Cite
|
Sign up to set email alerts
|

Tautomer Structures in Ketose–Aldose Transformation of 1,3-Dihydroxyacetone Studied by Infrared Electroabsorption Spectroscopy

Abstract: The acyclic form of monosaccharides exists in a structural equilibrium, with aldose having the aldehyde group and ketose the ketone group (ketose−aldose equilibrium). A basic catalyst facilitates their transformation, which affects the chemical properties of the monosaccharide. In this study, we investigated the ketose−aldose transformation of 1,3-dihydroxyacetone (1,3-DHA), one of the simplest systems of the ketose−aldose equilibrium. We examined the effects of piperidine as the basic catalyst and used IR ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…These experiments led to the observation that, at equilibrium, the mixture was composed of 60–65% DHA and 35–40% glyceraldehyde regardless of the starting point (pure DHA or pure Gld) [ 82 ]. This observation confirmed that DHA is more thermodynamically stable than Gld at room temperature ( Figure 8 ) [ 82 , 84 , 85 ].…”
Section: A Multi-functional Synthesis Tool: Dha’s Broad Range Of Reac...supporting
confidence: 72%
“…These experiments led to the observation that, at equilibrium, the mixture was composed of 60–65% DHA and 35–40% glyceraldehyde regardless of the starting point (pure DHA or pure Gld) [ 82 ]. This observation confirmed that DHA is more thermodynamically stable than Gld at room temperature ( Figure 8 ) [ 82 , 84 , 85 ].…”
Section: A Multi-functional Synthesis Tool: Dha’s Broad Range Of Reac...supporting
confidence: 72%
“…For DHA reduction, we hold first potential at 0 V versus RHE to collect the reference spectrum. When we applied negative potentials from 0 V to −1.1 V versus RHE, a positive band at 1736 cm –1 was observed, which could be assigned to CO stretching of the carbonyl group in DHA, indicating the consumption of DHA in the thin layer between the electrode and the prism. The peaks at 1431 and 1257 cm –1 are ascribed to CH 3 and CH 2 deformations and C–C–H deformation, respectively. , These features can be attributed to either the reactant DHA or the acetol, that is the first reduction product (see transmission spectra of DHA and acetol in Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate this possibility, we focused on controlling the fate of hemiaminal 21, the intermediate from which 5-OP-RU (kinetic product) or the lumazine (thermodynamic product via 23 and 24) would competitively form. We hypothesized that, as imine formation in polar solvents typically proceeds via the iminium intermediate (22), aprotic polar solvents might stabilize the cation while avoiding solvent attack on iminium 22, thus diverting the reaction toward 5-OP-RU.…”
Section: Synthesis Of 5-op-rumentioning
confidence: 99%
“… a Tautomerization and in situ dehydration of 1,3-dihydroxyacetone ( 14 ) to trace methylglyoxal ( 11 ) at 80 °C could produce 5-OP-RU ( 3 ) during the synthesis of rRL-6-HM ( 15 ). …”
Section: Discovery Of Antigens For Mait Cellsmentioning
confidence: 99%